2020
DOI: 10.1002/hyp.13883
|View full text |Cite
|
Sign up to set email alerts
|

On the controls of preferential flow in soils of different hillslope position and lithological origin

Abstract: Soils derived from different lithologies and their controls on preferential flow remain underexplored in forested landscapes. In the same lithology, the propensity for preferential flow occurrence at different hillslope positions also remains largely elusive. By utilizing a soil moisture response time method, we compared preferential flow occurrence between a shale site (Shale Hills, silt loam soils) and a sandstone site (Garner Run, sandy loam soils) at four hillslope positions: ridge-top, North-and South-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 72 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Data on hydrological and meteorological processes occurring in the CZO came from the large number of continuously operating instruments in this watershed (Brantley et al., 2016, 2018). GroundHOG sites (Brantley et al., 2016; Tang et al., 2020) recorded soil moisture and soil temperature separately at SPMS and SPVF and precipitation at SPMS (Eissenstat et al., 2020; Li & Eissenstat, 2020a, 2020b). Water levels were monitored in three wells near the SPMS and SPVF sites (CZMW8 at the ridge crest and Wells 5 and 7 at the valley floor) (Brantley & Gu, 2020a, 2020b, 2020c).…”
Section: Methodsmentioning
confidence: 99%
“…Data on hydrological and meteorological processes occurring in the CZO came from the large number of continuously operating instruments in this watershed (Brantley et al., 2016, 2018). GroundHOG sites (Brantley et al., 2016; Tang et al., 2020) recorded soil moisture and soil temperature separately at SPMS and SPVF and precipitation at SPMS (Eissenstat et al., 2020; Li & Eissenstat, 2020a, 2020b). Water levels were monitored in three wells near the SPMS and SPVF sites (CZMW8 at the ridge crest and Wells 5 and 7 at the valley floor) (Brantley & Gu, 2020a, 2020b, 2020c).…”
Section: Methodsmentioning
confidence: 99%
“…Initial soil water conditions were not identified as controlling factors in both forests, and this is consistent with Nimmo (2012) who argued that local saturation of soil was more likely to drive PF regardless of initial soil water conditions. Similarly, Wiekenkamp et al (2016) found no clear relationship between the PF frequency and initial soil water conditions when rainfall amount was less than 25 mm, and Tang et al (2020) found a significant effect of initial soil water conditions on PF occurrence at only one of three studied sites. Notably, soil moisture showed slight fluctuation owing to plentiful and concentrated throughfall during the monitoring period and was possibly far from the threshold of influencing PF occurrence (Figure S3).…”
Section: Discussionmentioning
confidence: 91%
“…An alternative method utilizing a high‐frequency soil moisture monitoring network was developed, which has advanced in‐situ detection of PF across spatial and temporal scales (Graham & Lin, 2011; Wiekenkamp et al, 2016). Using this method, researchers have gained a new understanding of PF relationships with watershed characteristics, such as rainfall events (Jost et al, 2012; Lozano‐Parra et al, 2015; Tian et al, 2019), soil depth and hillslope topography (Graham & Lin, 2011; Liu & Lin, 2015; Wiekenkamp et al, 2016), and initial soil water conditions and landforms (Demand et al, 2019; Holden, 2009; Liu & Lin, 2015; Tang et al, 2020). However, using a data‐intensive network‐based approach alone cannot resolve individual PF pathways or establish the continuity and possible soil depths of the PF processes.…”
Section: Introductionmentioning
confidence: 99%
“…In the Włocławek reservoir, in addition to the information on the sediments excavated in 2014-2019, in order to fully present this topic, it is also necessary to note that such activities have also recently been carried out, producing the following volumes of collected sediments: Dredging works on the Włocławek reservoir are mainly aimed at ensuring appropriate conditions for winter flood protection [54], including the permeability of the bed for ice flow in a longitudinal profile. Their importance was visible, e.g., in 2021, where, due to significant ice cover, the icebreaker action also reached an area of intense sediment accumulation.…”
Section: Figurementioning
confidence: 99%